The role of macroeconomic variables on Islamic stocks for achieving SDGs in Indonesia - Dina Yustisi Yurista; Rosida Dwi Ayuningtyas (Faculty of Economics, Universitas Islam Indonesia, 2019)
This paper aims to analyse macro-economic variables such as industrial production index (IPI), exchange rate, gross domestic product (GDP), and inflation which can affect the movement of Islamic stocks price in order to contribute the sustainable development goals in Indonesia. The methodology of this study is quantitative approach with Error Correction Model (ECM). The data is obtained from Bank Indonesia, Central bureau of statistics Indonesia and Indonesia Stock Exchange during period January 2013 to December 2018 quarterly. The findings showed that IPI has positive effect, while the exchange rate has a negative effect on Islamic stock price. Also GDP and inflation variables has negative in some companies and positive effect in other companies.